Legal Analysis of the Supreme Court Decision Regarding the Annulment of Acquittal in Corruption Crime Case: A Study of Decision Number 1227 K/Pid.Sus/2022 - Munthe, Raja Didit Pratama; Siregar, Ahmad Ansyari; Siahaan, Nimrot (SIGn Jurnal Hukum, 2025)
Law enforcement against corruption crimes in Indonesia is still characterized by a glaring disparity in decisions. This condition arises in a land procurement case in which the Judex Facti acquitted the defendant of the Public Prosecutor’s charges. This research aims to analyze the Supreme Court’s underlying legal considerations in annulling the Samarinda District Court’s acquittal. Additionally, this study reconstructs the unlawful element associated with the state land status and examines the validity of audit evidence relative to price appraisal. This research employs doctrinal legal research using the statute, case, and conceptual approaches. This study finds that the annulment of Decision Number 1/Pid.Sus-TPK/2021/PN Smr by Decision Number 1227 K/Pid.Sus/2022 was based on the Judex Facti’s fundamental error in making incorrect conclusions and legal considerations that were inconsistent with the facts revealed at trial. The analysis proves that former Right of Use land that has expired automatically reverts to a state asset by operation of law. Therefore, the compensation payment to a third party constitutes a fictitious act that fulfills the unlawful element and the element of abusing authority. This research concludes that the Audit Report declaring the occurrence of state losses is more valid than the procedurally flawed price-estimation assessment method conducted by telephone. As an implication, this research recommends a paradigm shift for judges from a formalistic-legal to a material-progressive approach in deciding cases. This research also urges the formulation of measurable sentencing guidelines to minimize verdict disparities and maximize state loss recovery.